Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/md18090461
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CAZy Repertoire from the Marine-Derived Fungus Stemphylium lucomagnoense in Relation to Saline Conditions

Abstract: Even if the ocean represents a large part of Earth’s surface, only a few studies describe marine-derived fungi compared to their terrestrial homologues. In this ecosystem, marine-derived fungi have had to adapt to the salinity and to the plant biomass composition. This articles studies the growth of five marine isolates and the tuning of lignocellulolytic activities under different conditions, including the salinity. A de novo transcriptome sequencing and assembly were used in combination with a proteomic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In a previous study, we showed that the presence of sea salt modified the composition of secreted lignocellulolytic enzymes, with increased secretion of xylanases and cellulases, and lower production of oxidoreductases belonging to the auxiliary activities (AA) class of the CAZy database [ 11 ]. This tendency was recently confirmed in the study of the marine-derived fungus Stemphylium lucomagnoense [ 12 ]. Although terrestrial basidiomycetes, particularly white-rot fungi, are seen as the key actors in environmental lignin degradation, marine-derived ascomycetes were also demonstrated to significantly degrade lignin [ 13 ].…”
Section: Introductionmentioning
confidence: 60%
“…In a previous study, we showed that the presence of sea salt modified the composition of secreted lignocellulolytic enzymes, with increased secretion of xylanases and cellulases, and lower production of oxidoreductases belonging to the auxiliary activities (AA) class of the CAZy database [ 11 ]. This tendency was recently confirmed in the study of the marine-derived fungus Stemphylium lucomagnoense [ 12 ]. Although terrestrial basidiomycetes, particularly white-rot fungi, are seen as the key actors in environmental lignin degradation, marine-derived ascomycetes were also demonstrated to significantly degrade lignin [ 13 ].…”
Section: Introductionmentioning
confidence: 60%
“…In previous work, we screened five fungal strains isolated from Tunisian coastal waters [26] and characterised for their laccase-like activities. Based on a microbial approach and on enzyme activity screening, one of these marine-derived strains, S. lucomagnoense, was selected for its adapted growth on xylan in saline conditions, and its improved laccase (seagrass-containing cultures) and cellulase (wheat straw-containing cultures) activities in the presence of sea salt [27]. To further study the selected marine-derived fungus, its transcriptome was sequenced and its proteome analysed when grown on wheat-straw and sea grass in the absence or presence of sea salt.…”
Section: Discussionmentioning
confidence: 99%
“…Stemphylium lucomagnoense was previously selected by screening fungi isolated from Tunisian coastal waters for its capacity to exert a laccase-like activity under saline conditions [26]. In addition, its secretome analysis confirmed the presence of laccase-like activities in the presence of sea salts [27]. In this study, we expressed a laccase encoding gene from S. lucomagnoense in Aspergillus niger and purified and characterised the corresponding protein to study the main properties of this marine-derived enzyme.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation